2017
DOI: 10.1139/apnm-2016-0608
|View full text |Cite
|
Sign up to set email alerts
|

The influence of genetic polymorphisms on performance and cardiac and hemodynamic parameters among Brazilian soccer players

Abstract: This study investigated whether ACTN3 R577X, AMPD1 C34T, I/D ACE, and M235T AGT polymorphisms can affect performance tests such as jumping, sprinting, and endurance in 220 young male athletes from professional minor league soccer team from São Paulo Futebol Clube, Brazil. I/D ACE and M235T AGT polymorphisms were also analyzed according to cardiac and hemodynamic parameters. Athletes were grouped or not by age. DNA from saliva and Taqman assays were used for genotyping 220 athletes and the results were associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 46 publications
4
29
0
1
Order By: Relevance
“…Endurance. The most studied polymorphisms were ACTN3 [1,15,20], ACE [20,21], AGT and AMPD [20], MTHFR [22], and GST [21]. Overall, 4 studies included young male football players and 1 involved youth female football players [1].…”
Section: Performancementioning
confidence: 99%
See 2 more Smart Citations
“…Endurance. The most studied polymorphisms were ACTN3 [1,15,20], ACE [20,21], AGT and AMPD [20], MTHFR [22], and GST [21]. Overall, 4 studies included young male football players and 1 involved youth female football players [1].…”
Section: Performancementioning
confidence: 99%
“…The association between the ACE and ACTN3 R577X polymorphisms and performance endurance was assessed in 4 studies [1,15,20,21]. Dinc et al [22] investigated athletic performance and homocysteine levels in relation to the MTHFR C677T mutation as well as its relationship with other cardiac risk factors.…”
Section: Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, regarding the influence of genetic variants on specific key factors in football performance, published findings are discordant. For example, some authors have found an interaction between polymorphisms and vertical jump height [13,26,29,36], short distance running speed and aerobic capacity [36], while other authors reported no association between genetic markers and quantitative traits of football performance [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, DD genotypes may benefit athletes in activities that require strength and speed, while II ACE genotype in endurance activities. 24 …”
mentioning
confidence: 99%